Incremental Validity of ADHD Dimensions in the Predictions of Emotional Symptoms, Conduct Problems, and Peer Problems in Adolescents Based on Parent, Teacher, and Self-Ratings - Rapson Gomez; Taylor Brown (Pediatric Reports)
Background: The present study investigated the incremental validity of the ADHD dimensions of inattention (IA), hyperactivity (HY), and impulsivity (IM) in the predictions of emotion symptoms (ESs), conduct problems (CPs), and peer problems (PPs) in adolescents based on parent, teacher, and self- ratings. Method: A total of 214 ratings were collected from adolescents, their parents, and teachers in Australia. A structural equation modeling approach was employed to evaluated incremental validity. Results: The findings revealed that, controlling for gender, IM contributed moderate, low, and low levels of variance in predicting ESs based on parent, teacher, and self-ratings, respectively. Additionally, IM contributed moderate, substantial, and moderate levels of variance to CP predictions based on parent, teacher, and self-ratings, respectively. Furthermore, after controlling for gender, IM, and HY, parent-rated IA contributed a low level of variance to the prediction of ESs, while teacher and self-rated IA did not contribute significantly to the prediction of ESs, CPs, or PPs. Conclusions: The findings underscore the differential predictive validity of ADHD dimensions across informants and outcomes, highlighting impulsivity’s stronger association with conduct problems and emotional symptoms. These results have theoretical and practical implications for understanding ADHD-related risks in adolescence and tailoring interventions accordingly.